The impact of attachment (site location) and view characteristics on the rental and open market values of commercial property (case study: shophouses in selected areas in Johor Bahru - Oliver, Valentine Eboy (UTM, 2004)
Site location or attachment and view characteristics are very important factors in determining the value of shop houses. Determining rental value is very important for investors in making decisions in shop houses investment. The rental and market value of shop houses differ from one to another depending on the site location. Therefore, this study will focused on the rental and market value of shop houses based on impact of attachment or site location factor. The purpose of this research is to find out what makes the differences in value among the shop houses in the area of Johor Bah u. The objectives of this study are to identify the factor and the impact of attachment and view factors on the rental and market values of shop houses in the selected area in Johor Bahru, to identify other determinant factors affecting values on property and to use GIS analysis for the rental and market value and display it in attractive and easy to understand. The factors affecting value and its importance are identifying using quantitative method. The relationship between these factors and the value was analyzed using the Multiple Regression Analysis and Correlation Analysis technique. The analysis result has succeeded in making a rental value model for shop houses. In conclusion, it is clearly shows that attachment (site location) and view characteristics are important factors in influencing the rental and market value of shop houses.